2019
DOI: 10.1002/adma.201900440
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Spherical Superstructure of Carbon Nanorods

Abstract: superstructure with a large radius of curvature, such as spherical organization, is still a challenge. So far, only a few kinds of 1D oxides could be assembled into 3D spherical superstructures. [13][14][15] Low-dimensional carbon nanomaterials have been widely used in energy storage and conversion owing to their distinct electrochemical properties and mechanical and thermal stability. [16][17][18] 3D superstructures constructed from lowdimensional components such as carbon nanorods/wires or graphene nanorribb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 39 publications
1
74
0
Order By: Relevance
“…23,24 Multiple research groups found that morphologies of MOF-74 could be altered by controlling the synthetic conditions, including chestnut-shell structures, superlong nanotubes, hollow tubes, ripened multichannel tubes and helical tubular structures. [25][26][27][28] Very recently, we found that by choosing a N,N-dimethylformamide (DMF) solvent as the reaction medium, the assembly of hierarchical superstructures could be accelerated, generating MOF-74 spherulites as a nal product (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Multiple research groups found that morphologies of MOF-74 could be altered by controlling the synthetic conditions, including chestnut-shell structures, superlong nanotubes, hollow tubes, ripened multichannel tubes and helical tubular structures. [25][26][27][28] Very recently, we found that by choosing a N,N-dimethylformamide (DMF) solvent as the reaction medium, the assembly of hierarchical superstructures could be accelerated, generating MOF-74 spherulites as a nal product (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Three‐dimensional superstructures with specific morphologies and functionalities have received substantial attention in chemistry and material science due to their potential applications [1–3] . In comparison with isolated building blocks (nanoparticles, nanorods, nanosheets, etc.…”
Section: Figurementioning
confidence: 99%
“…Three-dimensional superstructures with specific morphologies and functionalities have received substantial attention in chemistry and material science due to their potential applications. [1][2][3] In comparison with isolated building blocks (nanoparticles, nanorods, nanosheets, etc. ), which suffer from poor total conductivity, [4] well-defined arrangement of these nanostructures into 3D integrative networks of superstructures can show simultaneous electrical conductivity and porous channels for effective mass transport with retained their own functionality.…”
mentioning
confidence: 99%
“…[18][19][20] They have been used as precursors/templates for the synthesis of functional carbons and metal/ carbon composites with various controlled morphologies/structures and functionalities, showing a great potential in catalysis. [21][22][23][24][25] Generally, carbonization of MOFs produces collapsed structures or isolated carbon nanoparticles with insufficient contact and total conductivity. Thus, the transformation of MOFs into an active site-decorated carbon structure with simultaneous electrical conductivity and porous channels for fast electron transfer and effective mass transport, particularly in a self-templated or noncasting fashion, presents a major challenge.…”
Section: Doi: 101002/adma201904689mentioning
confidence: 99%